The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1044/jshr.3903.483
|View full text |Cite
|
Sign up to set email alerts
|

Preference for and Performance With Damped and Undamped Hearing Aids by Listeners With Sensorineural Hearing Loss

Abstract: This study investigated the relationship between acoustic damping of hearing aid responses and listeners’ speech discrimination and judgments of preference and sound quality. Eighteen subjects with essentially equivalent hearing impairments participated. Subjects’ speech discrimination was evaluated for a male talker in quiet and in noise and for a female talker in the same conditions with hearing aids with 0 dB, −5 dB, and −10 dB of damping. Subjects also compared the damping levels using eight bipolar adject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…There have been a number of studies which have documented differences in speech discrimination due to talker gender in hearing-impaired populations (Davis & Davidson, 1996;Stelmachowicz et al, 2002). There has also been considerable interest in the issue of phonetic balance (Eldert & Davis, 1951;Lehiste & Peterson, 1959;Martin et al, 2000).…”
Section: Sumariomentioning
confidence: 97%
“…There have been a number of studies which have documented differences in speech discrimination due to talker gender in hearing-impaired populations (Davis & Davidson, 1996;Stelmachowicz et al, 2002). There has also been considerable interest in the issue of phonetic balance (Eldert & Davis, 1951;Lehiste & Peterson, 1959;Martin et al, 2000).…”
Section: Sumariomentioning
confidence: 97%
“…Gabrielsson et al (1988) compared quality ratings for speech stimuli processed with several different frequency responses and reported that individuals with hearing loss preferred listening to speech with a frequency response that was flat in the low frequencies and had a ϩ6 dB/oct increase between 1000 and 4000 Hz. The presence of more spectral peaks has been shown to negatively impact the perception of hearing aid processed speech (e.g., Gabrielsson & Sjögren 1979;Davis & Davidson 1996;Warner & Bentler 2002). Low-frequency and high-frequency cutoffs also affect sound quality (Punch et al 1980;Tecca & Goldstein 1984;Punch & Beck 1986;.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have also found differences in speech audiometry results in hearing-impaired populations due to talker gender (Davis & Davidson, 1996;Stelmachowicz et al, 2002).…”
Section: Sumariomentioning
confidence: 96%